Analisis Efek Rembesan Air Sungai Lawai terhadap Kestabilan Rencana Lereng dengan Metode Morgenstern-Price pada Low Wall Tambang Air Laya Blok Barat PT. Bukit Asam Tbk, Tanjung Enim, Sumatera Selatan - Triliani Utami; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Bukit Asam using open pit method. Slopes are one of the most important factors in mining activities. Seepage is considering occur in location of studies in low wall of TAL, there is lawai river at the slope’s peak which can have an effect on the stability of the pit slope then analysis is needed. The analysis use Morgenstern-Price method with geotechnical software. The input data needed consists of rock lining material, material’s permeability, volumetric water content and data of physical and mechanical properties. Analysis of seepage and slope dissociation stability in 3 conditions of the river. The output of analysis are seepage discharge and safety factors. Seepage discharge during dry river is 8,131x10-6 m3/s with F/S 1,259, river conditions in partial height is 2.492x10-4 m3/s with F/S 1,171 and the river conditions in maximum height is 4,792x10-4 m3/s with F/S 1,110. The conclusion is water seepage has an effect on slope stability, the greater the seepage discharge so the smaller the F/S and the smaller the seepage discharge so the greater the F/S. Recommendation is needed by enlarging the slope angle, adding the benchs, cutting peak’s load around 556.43 m2/m and controlling river airflow at maximum height of 6 meters.Keywords: Slope Stability, Factor of Safety, Seepage, Seepage Discharge, Morgenstern-Price